The Aesthetic Appeal of the Literary Device “Talmeh” In the Works of Sayf Farg‘Oniy (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the use of the rhetorical device talmeh in the literary heritage of Sayf al-Din Muhammad Farg‘oniy, one of the prominent representatives of Persian-Tajik literature. Born in the 13th century in the Fergana Valley, Farg‘oniy was forced to leave his homeland due to the Mongol invasions. He spent a period in Tabriz and later settled in the present-day Turkish town of Aksaray, where he continued his literary activity until the end of his life. One of the essential aspects of poetic mastery lies in the skillful use of artistic devices. Like other classical poets, Sayf Farg‘oniy effectively employed figurative elements in his poetry, demonstrating both creativity and subtlety. He avoided redundancy in his thoughts and consistently strove to generate novel and multi-layered meanings. The poet utilized various stylistic techniques to enhance the richness and expressiveness of his ideas. His deliberate use of literary devices contributed significantly to the aesthetic appeal, semantic depth, and emotional resonance of his poetry.